2020
DOI: 10.3389/fmars.2019.00831
|View full text |Cite
|
Sign up to set email alerts
|

Contact- and Water-Mediated Effects of Macroalgae on the Physiology and Microbiome of Three Indo-Pacific Coral Species

Abstract: Fong et al. Macroalgal Effects on Corals coral microbiomes were sensitive to both direct contact and water-mediated interactions with macroalgae, while coral physiology was only compromised when in direct contact. Further, the presence of high levels of potentially pathogenic bacteria in some of the coral samples did not lead to the corals being more susceptible to impacts from macroalgae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
2
15
1
Order By: Relevance
“…As with growth, impacts on coral photosynthetic efficiency were only evident when corals were in direct contact with macroalgae. This is consistent with previous evidence [26], but we also found that effects varied depending upon the approach used for measuring ϕ PSII values. When measurements taken haphazardly around the coral were averaged to acquire a mean photosynthetic efficiency for each individual, ϕ PSII values were significantly less for corals in direct contact with Sargassum, but not Galaxaura.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As with growth, impacts on coral photosynthetic efficiency were only evident when corals were in direct contact with macroalgae. This is consistent with previous evidence [26], but we also found that effects varied depending upon the approach used for measuring ϕ PSII values. When measurements taken haphazardly around the coral were averaged to acquire a mean photosynthetic efficiency for each individual, ϕ PSII values were significantly less for corals in direct contact with Sargassum, but not Galaxaura.…”
Section: Discussionsupporting
confidence: 93%
“…This again suggests macroalgal impacts are contact-mediated. Previous studies have found evidence for water-mediated algal effects on coral microbial communities, but these were either conducted in mesocosms [26,27] or involved some degree of coral-algal contact when conducted in the field [21,52]. Differences in experimental design, duration, or species used may explain discrepancies between these studies and our findings.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Wainwright et al [13] attributed differences in coral microbiomes between Raffles and Kusu to the strong directionality of water movement from east to west differentially affecting the windward and leeward sides of Singapore's Southern Islands, particularly during the Northeast Monsoon [31]. The current study was conducted during the inter-monsoon period with light winds and relatively calm seas, which may explain why the coral microbiomes between the two reefs were not as divergent as in previous studies [13,30]. The mean seawater temperature of approximately 30 °C recorded at each reef and the nutrient concentrations are consistent with expectation for Singaporean waters [31,48].…”
Section: Discussionmentioning
confidence: 55%
“…This study focuses on Pocillopora acuta, a particularly resilient coral species found in relatively high abundance on reefs throughout Singapore's Southern Islands [25,29]. Previous studies have established that P. acuta located at Pulau Satumu (also referred to as Raffles Lighthouse) and Kusu Island, two of Singapore's Southern Islands separated by approximately 15 km, harbor distinct microbial communities, despite their spatial proximities [13,30]. The waters around the Southern Islands are thought to be well-mixed, but Kusu is located closer to the Singapore mainland and is therefore potentially more exposed to anthropogenic impacts [31].…”
Section: Introductionmentioning
confidence: 99%